Genetic Types, Distribution Patterns and Enrichment Mechanisms of Helium in China’s Petroliferous Basins - Qin, Shengfei; Xu, Dan; Li, Jiyuan; Zhou, Zheng (Frontiers in Earth Science, 2022)
Helium is a strategic resource with many scientific, technical and industrial applications. However, despite its importance and scarcity, there is a lack of understanding on its origin, migration and accumulation processes. In view of this, the distribution patterns and enrichment mechanisms of helium are studied based on systematic analysis of the genetic types of helium in petroliferous basins in China. The helium in the petroliferous basins in China is mainly radiogenic, which involves the decay of U and Th. As expected, we found that, in one gas field, the helium content in natural gas increases with the age of reservoir rock, and in the same layer of the same structure within one reservoir, the helium content in natural gas in high altitude part of the structure is higher than that in the lower part. Enrichment of helium is closely related to old deep groundwater. The helium produced by radioactive decay in old strata is dissolved in water and transported and enriched through water migration. Due to large uplift of the structure during the Himalayan period, the helium dissolved in water was exsolved and accumulated with natural gas in the trap above the water. And thus, the helium-rich natural gas reservoirs formed. So, the helium contents in natural gas fields increase gradually along the flow direction of groundwater. The area with large range of uplift often shows higher helium content. This study not only provides a basis for the study of helium enrichment research, but also provides a new idea for industrial helium resource exploration.